Summertime Atmospheric Boundary Layer Gradients of O2 and CO2 over the Southern Ocean - Morgan, Eric J.; Stephens, Britton B.; Long, Matthew C.; Keeling, Ralph F.; Bent, Jonathan D.; McKain, Kathryn; Sweeney, Colm; Hoecker‐martínez, Martín S.; Kort, Eric A. (Journal of Geophysical Research: Atmospheres, 2019)
We present airborne observations of the vertical gradient of atmospheric oxygen (Î´(O2/N2)) and carbon dioxide (CO2) through the atmospheric boundary layer (BL) over the Drake Passage region of the Southern Ocean, during the O2/N2 Ratio and CO2 Airborne Southern Ocean Study, from 15 January to 29 February 2016. Gradients were predominately anticorrelated, with excesses of Î´(O2/N2) and depletions of CO2 found within the boundary layer, relative to a mean reference height of 1.7Â km. Through analysis of the molar ratio of the gradients (GR), the behavior of other trace gases measured in situ, and modeling experiments with the Community Earth System Model, we found that the main driver of gradients was airâ sea exchange of O2 and CO2 driven by biological processes, more so than solubility effects. An exception to this was in the eastern Drake Passage, where positive GRs were occasionally observed, likely due to the dominance of thermal forcing on the airâ sea flux of both species. GRs were more spatially consistent than the magnitudes of the gradients, suggesting that GRs can provide integrated process constraints over broad spatial scales. Based on the model simulation within a domain bounded by 45Â°S, 75Â°S, 100Â°W, and 45Â°W, we show that the sampling density of the campaign was such that the observed mean GR (Â± standard error), â 4.0Â± 0.8 mol O2 per mol CO2, was a reasonable proxy for both the mean GR and the mean molar ratio of airâ sea fluxes of O2 and CO2 during the O2/N2 Ratio and CO2 Airborne Southern Ocean Study.Plain Language SummaryUsing an aircraft, we measured changes in atmospheric oxygen and carbon dioxide over the surface of the Southern Ocean. We show that these changes can be used to estimate the relative amounts of oxygen and carbon dioxide that the Southern Ocean exchanges in summer.Key PointsWe present atmospheric boundary layer gradients of oxygen and carbon dioxide over the Southern OceanGradients are driven primarily by airâ sea fluxes due to biological productionThe ratio of these ...